First Report of Blood Protozoa Infection in Wild-Caught Asian Vine Snake (Ahaetulla prasina) - Putri, Valerie Brilianda; Koesdarto, Setiawan; Yudhana, Aditya; Wardhana, April Hari; Wibawati, Prima Ayu; Santosa, Gusti Ayu Illiyin Putri; Tanjung, Aldi Gusnizar Rizaldy; Kurnianto, Muhammad Aqil; Khairunnisa, Hanifa Khansa (Journal of Basic Medical Veterinary, 2025)
The Asian vine snake (Ahaetulla prasina) is an arboreal snake that can inhabit various types of trees in both lowland and highland areas. Based on its habitat, the Asian vine snake has a high potential to be infected by parasites. One of the parasitic diseases that can infect snakes is blood protozoa, which have the potential to be zoonotic. It can be transmitted between animals and humans through food contamination due to environmental pollution by snake feces which contain infective stage of protozoa. Clinical symptoms of this infection include lethargy, dehydration, and anorexia, which are common signs of parasitism. Case reports related to blood protozoa in snakes in the Indonesia are still very limited and have never been reported in Asian vine snake, even though many people keep Asian vine snake as exotic pets.